Factors Affecting Occupational Safety Employee Organizations (Meta-Analysis of Available Research) - Masoud Hajizadeh Maymandi; Leili Bonyad (توسعه اجتماعی, 2020)
Occupational safety is one of the issues that have been considered by organizations, especially in recent decades. The complexity and increasing expansion of the division of labor process and the need for minor specialties in different fields require the use of various experts and technicians. In this regard, job security is one of the main concerns of the staff of the organizations. The present study aims to investigate the most important factors Effective job security in Iran has been carried out. In the method of meta-analysis, the statistical community includes all scientific-research papers that have come from reputable sites such as Noormgs, Magiran, the Comprehensive Human Sciences Portal and the Academic Database of Academic Jihad, and national and international conferences. The years of 2001 to 2017 were collected with the theme of job security finally, 19 studies were selected and analyzed CMA2 meta-analysis software. The findings of the study showed that the total of 28 variables of the three variables had the greatest impact on the job security of the employees. The results of the meta-analysis showed that the effect of employee empowerment and occupational safety with 0.57 and the magnitude of the effect of job satisfaction and job security were 0.52. Also, the relationship between organizational commitment and job security in the reviewed studies was 0.43 and moderately.